An Analysis of the Influence of Complaint Handling and the Quality of Hospital Services on Satisfaction and Patient Loyalty in Batubara Hospital - Tamimi Badzlina Nasution; Ermi Girsang; Sri Lestari Ramadhani Nasution (Sean Institute, 2024)
The patient satisfaction component is an important component of the quality of health services. Patients or the public who experience satisfaction with health services have a tendency for patients to follow advice and adhere to the treatment they are receiving, while patient dissatisfaction with health services tends to lead to non-compliance with treatment and moving to other health facilities.Patient loyalty is a patient's deep commitment to re-subscribe or re-purchase selected products or services consistently in the future, even though situational influences and some marketing efforts have the potential to cause behavior change. The aim of this research is to analyze the influence of complaint handling and the quality of hospital services on patient satisfaction and patient loyalty at Batubara Regional Hospital. The sample in this study amounted to 284 patients. The analysis used is univariate, bivariate and multivariate analysis. The results of this research showHandling complaints at RSUD Batubara, the majority of respondents answered good as many as 261 respondents, and respondents who answered not well were 23 respondents, the quality of hospital services at RSUD Batubara, the majority of respondents who answered good were 247 respondents, and those who answered not good were 37 respondents. 194 people were satisfied, and 90 people were dissatisfied, 193 patients with high loyalty and 91 patients with low loyalty,Handling complaints influences patient satisfaction and loyalty at Batubara Hospital. The quality of hospital services influences patient satisfaction and loyalty at Batubara Hospital.